FACTORS INFLUENCING THE ADOPTION OF SOLAR-POWERED COLD STORAGE TECHNOLOGY IN AMONG VEGETABLE MARKETERS IN NORTHEAST, NIGERIA - Manu, I.; Abdullahi, S.; Danwanka, H.A.; Sani, R.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the factors influencing adoption of solar powered cold storage technology in Northeast, Nigeria. A multi-stage sampling technique was used to select 455 vegetable marketers from the study area. Primary data were collected using structured questionnaires and analyzed using descriptive and inferential statistics. The results showed that the respondents had a mean age, household size, marketing experience and income of 43 years, 10 persons, 23 years and ₦174,516.85, respectively. Furthermore, most (97% and 95%) of the respondents were males and married while majority (85%) had secondary education. Most (93% and 99.2%) of the respondents belong to cooperative society and had no access to extension services. The results also revealed that the technology offers significant improvements over existing technologies and it is compatible with the existing values and needs of vegetable marketers with a mean of 2.9, respectively. The technology is easy to understand and can be experimented on a limited scale, with a mean of 2.6 and 2.4, respectively. The result further revealed that the advantage of the technology can be easily observed and measured (2.5), accessible (2.3), affordable (1.7) and practiced with low risk (2.3). The logit regression result revealed that marital status and membership of cooperatives were positive and significant (P˂0.05) while, monthly income was positive and significant (P˂0.01) in influencing the adoption of solar powered cold storage. The study concluded that marital status, membership of cooperative societies and monthly income were the significant factors influencing the adoption of solar powered cold storage technology in the study area. The study therefore, recommends that, Government, NGOs and financial institutions should collaborate to provide financial assistance such as low-interest loans, grants, or subsidies to the marketers, vegetable marketers should partner with solar technology companies to develop affordable cold storage solutions that suit their financial capacities and government and private sector stakeholders should prioritize funding and constructing additional cold storage facilities for vegetable marketers.